Observations of Low-frequency Radio Emission from Millisecond Pulsars and Multipath Propagation in the Interstellar Medium - Bhat, Ramesh; Tremblay, S.; Kirsten, Franz; Meyers, B.; Sokolowski, Marcin; Straten, W.; McSweeney, S.; Ord, S.; Shannon, Ryan; Beardsley, A.; Crosse, B.; Emrich, David; et al. (Institute of Physics Publishing, 2018)
© 2018. The American Astronomical Society. All rights reserved. Studying the gravitational-wave sky with pulsar timing arrays (PTAs) is a key science goal for the Square Kilometre Array (SKA) and its pathfinder telescopes. With current PTAs reaching sub-microsecond timing precision, making accurate measurements of interstellar propagation effects and mitigating them effectively has become increasingly important to realize PTA goals. As these effects are much stronger at longer wavelengths, low-frequency observations are most appealing for characterizing the interstellar medium (ISM) along the sight lines toward PTA pulsars. The Murchison Widefield Array (MWA) and the Engineering Development Array (EDA), which utilizes MWA technologies, present promising opportunities for undertaking such studies, particularly for PTA pulsars located in the southern sky. Such pulsars are also the prime targets for PTA efforts planned with the South African MeerKAT, and eventually with the SKA. In this paper we report on observations of two bright southern millisecond pulsars, PSR J0437-4715 and PSR J2145-0750, made with these facilities; MWA observations sampled multiple frequencies across the 80-250 MHz frequency range, while the EDA provided direct-sampled baseband data to yield a large instantaneous usable bandwidth of ~200 MHz. Using these exploratory observations, we investigate various aspects relating to pulsar emission and ISM properties, such as spectral evolution of the mean pulse shape, scintillation as a function of frequency, chromaticity in interstellar dispersion, and flux density spectra at low frequencies. Systematic and regular monitoring observations will help ascertain the role of low-frequency measurements in PTA experiments, while simultaneously providing a detailed characterization of the ISM toward the pulsars, which will be useful in devising optimal observing strategies for future PTA experiments.